The U.S Subprime Mortgage Crisis: An analysis of Rating Transitions and The Role of Credit Rating Agencies - Sethi, Rahul (2008)
The ongoing credit crisis has virtually engulfed all the biggest financial markets in the world and an end to this turmoil seems very far off at this moment in time. But it is very essential to understand the root cause of this crisis, which began in mid-2007 in the United States of America due to the collapse of the housing market. This paper starts with the factors leading to the crisis and focuses on one of the key players in this whole fiasco that played a very pivotal role in the origination of this crisis and that is The Credit Rating Agencies.